Coronary artery vasospasms in a microminipig occurred after placing an ameroid constrictor - CAO, Xin (J Vet Med Sci, 2016)
A 12-month-old microminipig, weighing 12.6 kg, showed 3 repeated episodes of transient ST-segment elevation in 24 hr Holter electrocardiogram after placing an ameroid constrictor around the left anterior descending coronary artery. Ventricular fibrillation was noticed just after the cessation of the 24 hr Holter-electrocardiogram recording. Direct current defibrillations and cardiopulmonary resuscitation were performed; however, they were unsuccessful, leading to the animal’s death. Its heart was excised for macroscopic analysis, which indicated that lumen of the ameroid constrictor was not narrowed and that there was no dissection, embolus or thrombus in the coronary arteries, indirectly suggesting that coronary artery vasospasm may have caused the ischemic attacks. Thus, microminipig may possess some potential to have coronary vasospasm.